THE EFFECT OF AN EDUCATIONAL PROGRAM BASED ON BRAIN-DIRECTED MOTOR EXERCISES ON THE SKILL PERFORMANCE LEVEL OF TECHNICAL STAGES AND THE DIGITAL ACHIEVEMENT LEVEL IN THE TRIPLE JUMP EVENT - Asst. Prof. Dr. Ihsan Qaddoori Ameen (Proximus Journal Publishing, 2025)
The study's goal was to ascertain the effects of an educational program focused on brain-directed motor exercises on the skill performance level of the technical stages and the digital achievement level of the triple jump event. The researcher anticipated that there would be a statistically significant difference between the experimental and control groups in the skill performance level of the triple jump phases and digital achievement, preferring the experimental group.
Keywords: preferring; digital achievement; statistically